Visualization analysis on the research topic and hotspot of online learning by using CiteSpace—Based on the Web of Science core collection (2004–2022) - Shen, Youhua; Huang, Lehui; Wu, Xueshi (Frontiers in Psychology, 2022)
The objective of this research is to establish a better understanding of the current landscape of online learning research and development by using CiteSpace's visual analysis. First, we retrieved published publications from the Web of Science (2004–2022). Following that, we examined the primary research strengths and important subjects of online learning from two perspectives: collaboration networks (including collaborative networks across countries, institutions, and authors) and co-citation networks. We examined the co-citation network from three perspectives: cluster analysis, the most active citers, top references. Furthermore, referenced journals, popular themes, and rising trends were examined. These findings indicate the primary study subjects in the field of online learning, the most intriguing research literature, and each period's emerging research hotspots. Finally, we proposed further study ideas for future paths.